Moving toward nutrition-sensitive agriculture strategies and programming in Ethiopia - Bossuyt, Anne (International Food Policy Research Institute, 2019)
This chapter begins with a discussion of Ethiopia’s various nutrition-related indicators, which show the persistence of child and adult malnutrition, despite some progress. It discusses the major programs and policies that have been launched during the past two decades within the nutrition and agriculture sectors, and at the global level too, and the synergies (and remaining gaps) between them. The sum of these developments reflect Ethiopia’s slow but promising shift to a coordinated, multisectoral approach to improving nutrition.